PSV-31 Influence of Hempseed Meal Supplementation on Fresh and Cooked Characteristics of Boer Cross Goats. (30th November 2020) - Smith, Hunter R; Abrahamsen, Frank W; Rehm, John G; Wilborn, Barney; Blythe, Eugene; Sawyer, Jason T; Gurung, Nar
Abstract: Hempseed meal is byproduct of hemp oil production and is relatively high in fiber, fat, and protein, making it a potential feedstuff for ruminants. However, the impact this new byproduct could have on meat characteristics is unknown. The objective of the current study was to evaluate the impact of HSM on fresh and cooked characteristics of Spanish meat goat retail cuts. Forty Boer crossbred castrated male goats were randomly allocated to one of four diets (n = 10; 0, 10, 20 or 30%) containing HSM which originated from the manufacturing industry of hemp oil. Goats were provided 2 kg of diet daily that contained varying levels of HSM in addition to ad-libitum access to water throughout the study. Following a 60-day feeding period goats were harvested at the Lambert-Powell Meats Laboratory located at Auburn University. After chilling for 12 h at 0°C, carcass measurements were collected prior to carcass fabrication. Goat carcasses were fabricated into wholesale cuts of the shoulder, rack, loin and leg. Paired loins and legs were sliced into 2.54-cm-thick chops, vacuum packaged, and assigned to cook yield, instrumental fresh color, and instrumental tenderness and frozen at -23°C until all laboratory analysis could be completed. The use of HSM did not alter cooking yield in either the goat loin or leg chop (P > 0.05) regardless of inclusion percentage within the diet. Furthermore, Warner-Bratzler shear force (WBSF) did not differ (P > 0.05) with increasing inclusion rates of HSM for either the loin or leg chops. Instrumental color for lightness (L*) or yellowness (b*) did not differ (P > 0.05) across diet treatments for either the loin or leg chops. These findings suggest that the inclusion of HSM within the diet of Boer cross goats did not alter fresh or cooked meat characteristics in either the loin or leg chops.